Establishment of Individual Limited Liability Company - Aprinawati; Desti Arliani; Irvan Riski Marnoran Saragih; Hanna Mutiakasih Damanik; Lila Ines Geshia Br Ginting; Tiara Fadillah (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the business world, many entrepreneurs choose Individual Limited Liability Companies (PT) in running their businesses. There are many reasons why entrepreneurs choose this, including because capital/shares have assets that are separate from the assets of the shareholders, shareholders have limited responsibility, there is a separation of functions between shareholders and management or directors, and the highest authority is exercised by the organs of the company, namely the General Meeting of Shareholders, the Board of Directors and the Board of Commissioners together. The research method for this article is library research. Even though there is only one founder, it is necessary to emphasize that an individual PT has the same legal status as the PT that we have known so far, with at least 2 shareholders and founders (hereinafter referred to as an ordinary PT).